Women on the Move: How Socio-Economic Background Through Lifestyle Shapes Travel Behavior to Bali - Kurniasari, Ni Made Dyah Ryana; Yudhistira, Putu Gde Arie (Universitas Brawijaya, Indonesia, 2025)
Tourism is a crucial sector for economic growth, and understanding the factors that influence travel behavior is essential for developing effective strategies. This study aims to investigate the influence of socio-economic and lifestyle factors on women's travel behavior to Bali, incorporating the moderating roles of social media use and collectivism. Using a modified version of the Theory of Planned Behavior (TPB), this study adopts a quantitative approach. Data were collected from 365 female respondents through a judgmental sampling technique and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings revealed that socio-economic status significantly impacts travel behavior, with lifestyle mediating. Additionally, collectivism moderates the relationship between socio-economic status and travel behavior. This study contributes to tourism research by enhancing the TPB framework and addressing gender-specific travel behaviors. The novelty lies in its focus on the interplay between socio-economic, cultural, and technological factors. It provides valuable insights for gender-responsive tourism strategies and inclusive, social media-driven marketing approaches in Bali.